Educational Transformation: Technology Axiology and Humanistic Values in Digital Learning - Rosidin, Rosidin; Herpratiwi, Herpratiwi; Sutiarso, Sugeng; Nurwahidin, Muhammad; Firdaus, Rangga (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
Humanistic theory is famous for its view that humans are humans, meaning that humans are living creatures created by the Creator who have their own nature to stand on this earth. In addition, this theory is characterized by an effort to observe individual or student behavior from the angle of the student or the culprit, not from the teacher or observer. This scientific article was prepared using the systematic literature review (SLR) method. The SLR method is used to identify, review, evaluate, and interpret all available research with the topic area of the phenomenon of interest. Researchers selected 7 articles that were related to the keywords used from 2015 to 2023. Educational transformation that combines technological axiology and humanistic values in digital learning is a positive step to form a generation that is technologically intelligent and also equipped with strong human values. This kind of education is expected to create individuals who are able to face future challenges wisely and contribute positively to the global community.